RESISTANCE TEST OF GRAM NEGATIVE ROD BACTERIA THAT CAUSE URINARY TRACT INFECTIONS (UTI) TO THE ANTIBIOTICS AMOXICILIN, GENTAMICIN, AND TETRACYCLINE IN ELDERLY WOMEN IN KRATONAN VILLAGE, SURAKARTA - Pembayun, Raflesia Rasmiati Putri; Silviani, Yusianti (Pharmaqueous: Jurnal Ilmiah Kefarmasian, 2024)
Urinary tract infection (UTI) is an infection caused by bacteria, especially gram-negative rod bacteria. Gram-negative rod bacteria that can cause UTIs are Escherichia coli, Klebsiella sp, Proteus sp, Enterococcus sp, Enterobacter sp, and Pseudomonas sp. Treatment to treat cases of bacterial infections using antibiotics. The purpose of this study was to determine the resistance of gram-negative rod bacteria that cause urinary tract infections (UTIs) to antibiotics amoxicilin, gentamicin, and tetracycline. The type of research used in this Scientific Paper is observational descriptive research. This research was conducted at the Bacteriology Laboratory of the Sekolah Tinggi Ilmu Kesehatan Nasional. The sampling technique used is quota sampling. The sample used was the urine of elderly women in the Surakarta Kratonan Village area. Urine samples were cultured using BHI media, and then gram painting was done. Culture results are inoculated on Mac Conkey media, and after the colony grows continued inoculation on biochemical test media to determine the bacterial species. Bacterial species were found to be tested for antibiotic resistance by the Kirby-Bauer method. The results showed that there were several species of bacteria resistant to antibiotics amoxicilin, gentamicin, and tetracycline. In Escherichia coli bacteria (60%) resistant to the antibiotic amoxicilin, and (40%) tetracycline; Klebsiella pneumoniae (50%) resistant to antibiotics amoxicilin and (25%) tetracycline; Klebsiella oxytoca (100%) resistant to antibiotics amoxicilin and (100%) tetracycline; Proteus mirabilis (100%) is resistant to the antibiotics amoxicilin, (100%) gentamicin, and (100%) tetracycline.